Cluster M mycobacteriophages Bongo, PegLeg, and Rey with unusually large repertoires of tRNA isotypes - Pope, Welkin H; Anders, Kirk R; Baird, Madison A; Bowman, Charles A; Boyle, Michelle M; Broussard, Gregory W; Chow, Tiffany W; Clase, Kari; Cooper, Shannon D; Cornely, Kathleen; Dejong, Randall J; Delesalle, Veronique A; et al. (Journal of Virology, 2014)
Genomic analysis of a large set of phages infecting the common host Mycobacterium smegmatis mc2155 shows that they span considerable genetic diversity. There are more than 20 distinct types that lack nucleotide similarity with each other, and there is considerable diversity within most of the groups. Three newly isolated temperate mycobacteriophages, Bongo, PegLeg, and Rey, constitute a new group (cluster M), with the closely related phages Bongo and PegLeg forming subcluster M1 and the more distantly related Rey forming subcluster M2. The clusterMmycobacteriophages have siphoviral morphologies with unusually long tails, are homoimmune, and have larger than average genomes (80.2 to 83.7 kbp). They exhibit a variety of features not previously described in other mycobacteriophages, including noncanonical genome architectures and several unusual sets of conserved repeated sequences suggesting novel regulatory systems for both transcription and translation. In addition to containing transfer-messenger RNA and RtcB-like RNA ligase genes, their genomes encode 21 to 24 tRNA genes encompassing complete or nearly complete sets of isotypes. We predict that these tRNAs are used in late lytic growth, likely compensating for the degradation or inadequacy of host tRNAs. They may represent a complete set of tRNAs necessary for late lytic growth, especially when taken together with the apparent lack of codons in the same late genes that correspond to tRNAs that the genomes of the phages do not obviously encode. © 2014, American Society for Microbiology.
Keywords: Base Composition; Base Sequence; Codon; Conserved Sequence; DNA binding motif; DNA sequence; Gene Order; Genome Size; Genome, Viral; Inverted Repeat Sequences; Lysogeny; Multigene Family; Mycobacteriophages; Mycobacterium smegmatis; Open Reading Frames; Phylogeny; RNA cleavage; RNA degradation; RNA translation; RNA, Transfer; RNA, Viral; Repetitive Sequences, Nucleic Acid; Sequence Alignment; Virion; Virus Assembly; article; controlled study; dept.bio; gene cassette; gene control; gene structure; genetic analysis; genetic transcription; genetic variability; membrane protein; mycobacteriophage; mycobacteriophage Bongo; mycobacteriophage M; mycobacteriophage Pegleg; mycobacteriophage Rey; nonhuman; nucleotide sequence; priority journal; protein gp19; protein gp23; protein gp24; protein gp26; protein gp30; protein gp31; protein gp39; single stranded DNA binding protein; tmp gene; transfer RNA; unclassified drug; viral genetics; virus assembly; virus classification; virus immunity; virus morphology

Prophage-mediated defence against viral attack and viral counter-defence. - Dedrick, Rebekah M; Jacobs-Sera, Deborah; Bustamante, Carlos A Guerrero; Garlena, Rebecca A; Mavrich, Travis N; Pope, Welkin H; Reyes, Juan C Cervantes; Russell, Daniel A; Adair, Tamarah; Alvey, Richard; Bonilla, J Alfred; Bricker, Jerald S; et al. (Nature Microbiology, 2017)
Temperate phages are common, and prophages are abundant residents of sequenced bacterial genomes. Mycobacteriophages are viruses that infect mycobacterial hosts including Mycobacterium tuberculosis and Mycobacterium smegmatis, encompass substantial genetic diversity and are commonly temperate. Characterization of ten Cluster N temperate mycobacteriophages revealed at least five distinct prophage-expressed viral defence systems that interfere with the infection of lytic and temperate phages that are either closely related (homotypic defence) or unrelated (heterotypic defence) to the prophage. Target specificity is unpredictable, ranging from a single target phage to one-third of those tested. The defence systems include a single-subunit restriction system, a heterotypic exclusion system and a predicted (p)ppGpp synthetase, which blocks lytic phage growth, promotes bacterial survival and enables efficient lysogeny. The predicted (p)ppGpp synthetase coded by the Phrann prophage defends against phage Tweety infection, but Tweety codes for a tetrapeptide repeat protein, gp54, which acts as a highly effective counter-defence system. Prophage-mediated viral defence offers an efficient mechanism for bacterial success in host-virus dynamics, and counter-defence promotes phage co-evolution.
Keywords: *Mycobacteriophages/ph [Physiology]; *Mycobacterium smegmatis/vi [Virology]; *Mycobacterium tuberculosis/vi [Virology]; *Prophages/ph [Physiology]; DNA, Viral; DNA, Viral/ge [Genetics]; Genetic Variation; Genome, Bacterial; Genome, Viral; Ligases; Ligases/ge [Genetics]; Lysogeny; Mycobacteriophages; Mycobacteriophages/ge [Genetics]; Mycobacterium smegmatis; Mycobacterium smegmatis/ge [Genetics]; Mycobacterium tuberculosis; Mycobacterium tuberculosis/ge [Genetics]; Phylogeny; Prophages; Prophages/en [Enzymology]; Prophages/ge [Genetics]; Viral Proteins; Viral Proteins/ge [Genetics]; bacterial genome; dept.bio; enzymology; genetic variation; genetics; guanosine 3',5'-polyphosphate synthetases; ligase; lysogenization; mycobacteriophage; phylogeny; physiology; prophage; viral protein; virology; virus DNA; virus genome

Models of classroom assessment for course-based research experiences - Hanauer, David I.; Zhang, Tong; Graham, Mark J.; Adams, Sandra D.; Ahumada-Santos, Yesmi Patricia; Alvey, Richard M.; Antunes, Mauricio S.; Ayuk, Mary A.; Elena Báez-Flores, María; Bancroft, Christa T.; Bates, Tonya C.; Bechman, Meghan J.; et al. (Frontiers in Education, 2023)
Course-based research pedagogy involves positioning students as contributors to authentic research projects as part of an engaging educational experience that promotes their learning and persistence in science. To develop a model for assessing and grading students engaged in this type of learning experience, the assessment aims and practices of a community of experienced course-based research instructors were collected and analyzed. This approach defines four aims of course-based research assessment—(1) Assessing Laboratory Work and Scientific Thinking; (2) Evaluating Mastery of Concepts, Quantitative Thinking and Skills; (3) Appraising Forms of Scientific Communication; and (4) Metacognition of Learning—along with a set of practices for each aim. These aims and practices of assessment were then integrated with previously developed models of course-based research instruction to reveal an assessment program in which instructors provide extensive feedback to support productive student engagement in research while grading those aspects of research that are necessary for the student to succeed. Assessment conducted in this way delicately balances the need to facilitate students’ ongoing research with the requirement of a final grade without undercutting the important aims of a CRE education.
Keywords: dept.bio; peer-reviewed